Effect of high MgO/Al2O3ratio (1.2 to 2.2) on sintering behavior and metallurgical properties - Ju J.-T.; Tang C.-M.; Pang Z.-G.; Xing X. -D.; Ji G.-H. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The sintering pot test was used to investigate the effect of MgO/Al2O3 ratio in the range of 1.2 to 2.2 on the sintering behavior of iron ore. The main characterization methods of X-ray diffraction (XRD) and scanning electron microscopyenergy disperse spectroscopy (SEM-EDS) were employed. The results showed that the strength, yield, and reducibility of sinter initially increased and then decreased with increasing MgO/Al2O3 ratio from 1.2 to 2.2. The index would reach the peak value with the strength of 70.6% and the yield of 83.81%, respectively, when MgO/Al2O3 ratio was 1.8. The reduction index would reach the peak value of 88.54% with MgO/Al2O3 ratio of 1.6. The FeO content, solid fuel consumption, and the RDI+3.15 of sinter increased dramatically with increasing MgO/Al2O3 ratio. When MgO/Al2O3 ratio was up to 2.2, the solid fuel consumption and RDI+3.15 reached a maximum value of 61.93 kg/t and 96.1%, respectively. The form of SFCA was acicular when MgO/Al2O3 ratio was less than 1.6 and then transformed to plate-like which content also reduced. The magnetite increased while hematite decreased with enhancing MgO/Al2O3 ratio.